Bladder Cancer Screening in Aluminum Smelter Workers. Issue 4 (April 2015) - Taiwo, Oyebode A.; Slade, Martin D.; Cantley, Linda F.; Tessier-Sherman, Baylah; Galusha, Deron; Kirsche, Sharon R.; Donoghue, A. Michael; Cullen, Mark R.
Abstract : Objective: To present results of a bladder cancer screening program conducted in 18 aluminum smelters in the United States from January 2000 to December 2010. Methods: Data were collected on a cohort of workers with a history of working in coal tar pitch volatile exposed areas including urine analysis for conventional cytology and ImmunoCyt/uCyt+ assay. Results: ImmunoCyt/uCyt+ and cytology in combination showed a sensitivity of 62.30%, a specificity of 92.60%, a negative predictive value of 99.90%, and a positive predictive value of 2.96%. Fourteen cases of bladder cancer were detected, and the standardized incidence ratio of bladder cancer was 1.18 (95% confidence interval, 0.65 to 1.99). Individuals who tested positive on either test who were later determined to be cancer free had undergone expensive and invasive tests. Conclusions: Evidence to support continued surveillance of this cohort has not been demonstrated.